Analysis of the impact of the electric peak and plate on labor productivity and economic performance in Ecuador 2024 - Laines Álvarez, Yolanda María; Medina Cubillo, Emily Nerea; Tinizaray Castro , Allison Jamileth; Arrobo Álvarez , Doris Madeleyn; Loaiza Condoy , Camila Estefanía (Revista Universidad de Guayaquil, 2025)
This study analyzes how the "Electric Peak and Plate" measure, implemented in Ecuador in 2024, has changed the way companies work and face the energy crisis. Through the review of articles, reports and documents, it sought to understand how this regulation, which adjusts working hours, has helped to maintain operations despite power outages. While the move has allowed many businesses to continue operating, it has also brought major challenges, especially for small businesses, which have had to deal with higher costs and difficulties adapting. Even so, some companies have taken advantage of the situation to innovate and improve their energy efficiency. In short, although the "Electric Peak and Plate" has been a temporary solution, it is clear that it is necessary to think about sustainable strategies and greater support for the most affected sectors.
Keywords: crisis management; costs; Electric Peak and Plate; labor productivity